Graham Greene’s Visit to Pazo de Barrantes in 1987 - Villar Flor, Carlos (Madrygal. Revista de Estudios Gallegos, 2018)
From 1976 the English novelist Graham Greene began to travel periodically to Spain at the invitation of his friend, Leopoldo Durán Justo, a Galician priest and lecturer at the Universidad Complutense de Madrid. A tradition of annual holidays in the Iberian Peninsula thus began, reaching a total of fifteen visits until the death of the author in 1991. From this first trip Greene had the opportunity to tour numerous Galician sites, many of which would become compulsory stops, but the one of 1987 is of special interest to understand his personal relationship with Galicia. The itinerary this summer was marked by the invitation of the Galician entrepreneur Vicente Cebrián, Count of Creixell, to visit the headquarters of the Murrieta wineries and to stay three days in the Pazo de Barrantes, in Pontevedra. The Count's hospitality was accompanied by a proposal to the writer: to agree to lend his name to an initiative he was contemplating, the Graham Greene Foundation. The present article reconstructs the fourteenth and penultimate trip of Greene to Spain from biographical notes taken by Durán that were never made public, and from an exceptional diary outlined by Greene himself. Thus, it offers unpublished information to recreate the main anecdotes that took place, paying special attention to the days that the travellers spent at the Pazo de Barrantes as guests of the Counts of Creixell.
Keywords: Graham Greene; Leopoldo Durán; Travel Literature; Graham Greene Foundation; Pazo de Barrantes.